Depleting components of the THO complex causes increased telomere length by reducing the expression of the telomere-associated protein Rif1p. - Tai-Yuan Yu (Public Library of Science (PLoS), 2012)
Telomere length is regulated mostly by proteins directly associated with telomeres. However, genome-wide analysis of Saccharomyces cerevisiae mutants has revealed that deletion of Hpr1p, a component of the THO complex, also affects telomere length. The THO complex comprises four protein subunits, namely, Tho2p, Hpr1p, Mft1p, and Thp2p. These subunits interplay between transcription elongation and co-transcriptional assembly of export-competent mRNPs. Here we found that the deletion of tho2 or hpr1 caused telomere lengthening by ∼50-100 bps, whereas that of mft1 or thp2 did not affect telomere length. Since the THO complex functions in transcription elongation, we analyzed the expression of telomere-associated proteins in mutants depleted of complex components. We found that both the mRNA and protein levels of RIF1 were decreased in tho2 and hpr1 cells. RIF1 encodes a 1917-amino acid polypeptide that is involved in regulating telomere length and the formation of telomeric heterochromatin. Hpr1p and Tho2p appeared to affect telomeres through Rif1p, as increased Rif1p levels suppressed the telomere lengthening in tho2 and hpr1 cells. Moreover, yeast cells carrying rif1 tho2 or rif1 hpr1 double mutations showed telomere lengths and telomere silencing effects similar to those observed in the rif1 mutant. Thus, we conclude that mutations of components of the THO complex affect telomere functions by reducing the expression of a telomere-associated protein, Rif1p.